2015
DOI: 10.1108/ejm-11-2013-0630
|View full text |Cite
|
Sign up to set email alerts
|

Effectuation and foreign market entry of entrepreneurial firms

Abstract: Purpose: The purpose of this study is to examine the decision-making process for entrepreneurial firms when entering foreign markets and how and why they entered those markets.Design/methodology/approach: We combine a nascent theory in entrepreneurship called effectuation with internationalization process theory as the conceptual framework to study decision-making under uncertainty. The central concept in both these theories is relationships and how they can be used to gain knowledge and thus reduce uncertaint… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

5
97
0
4

Year Published

2017
2017
2024
2024

Publication Types

Select...
4
2

Relationship

0
6

Authors

Journals

citations
Cited by 114 publications
(106 citation statements)
references
References 75 publications
5
97
0
4
Order By: Relevance
“…Opportunity evaluation is central to the study of the entrepreneur's cognitive processes in international decisions and, arguably, remains underexplored and poorly understood (Lamb et al, 2011;Maitland & Sammartino, 2015;Zahra et al, 2005). Scholars have recently begun to link internationalization and effectuation theory (e.g., Kalinic et al, 2014;Chetty et al, 2015) yet very little research explicitly studies the role of time and its impact on international entrepreneurial opportunity (IEO) evaluation and actualization. By interviewing the founders of 15 early-internationalizing small to medium sized firms in Australia from 2005 to 2012, this study explores and answers the primary research question: How do entrepreneurs evaluate international entrepreneurial opportunities (IEOs)?…”
Section: Discussionmentioning
confidence: 99%
See 4 more Smart Citations
“…Opportunity evaluation is central to the study of the entrepreneur's cognitive processes in international decisions and, arguably, remains underexplored and poorly understood (Lamb et al, 2011;Maitland & Sammartino, 2015;Zahra et al, 2005). Scholars have recently begun to link internationalization and effectuation theory (e.g., Kalinic et al, 2014;Chetty et al, 2015) yet very little research explicitly studies the role of time and its impact on international entrepreneurial opportunity (IEO) evaluation and actualization. By interviewing the founders of 15 early-internationalizing small to medium sized firms in Australia from 2005 to 2012, this study explores and answers the primary research question: How do entrepreneurs evaluate international entrepreneurial opportunities (IEOs)?…”
Section: Discussionmentioning
confidence: 99%
“…For instance, Kalinic et al (2014) argued that entrepreneurs prefer the causal over the effectual approach if the information is available and the company has the resources, and they asserted that entrepreneurs switch between causal and effectual logic when problems appear too complex. Chetty et al (2015) propose that ''it is meaningless to consider causation and effectuation as opposites of a continuum but to consider them as substitutes'' and that ''these logics are not linear but are nuanced as they intertwine during decision-making and actual implementation'' (Chetty et al, : 1453. Harms and Schiele (2012: 95) found that ''experienced entrepreneurs tend to apply effectuation rather than causation.'…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations